2018
DOI: 10.1039/c8md00055g
|View full text |Cite
|
Sign up to set email alerts
|

Triazole–diindolylmethane conjugates as new antitubercular agents: synthesis, bioevaluation, and molecular docking

Abstract: We describe the synthesis of novel triazole-incorporated diindolylmethanes (DIMs) using a molecular hybridization approach. The antitubercular activity of the DIMs against H37Ra (ATCC 25177) was tested in the active and dormant state. Among all the synthesized conjugates, the compounds ,, ,, ,, and displayed good antitubercular activity against both the active and dormant H37Ra strain. The compound exhibited good antitubercular activity against dormant H37Ra with an IC value of 1 μg mL and IC (MIC) value of 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…The in vitro anti-tubercular properties of the triazole-indole hybrid derivatives were evaluated against M. tuberculosis H37Ra in the active and dormant state. 107 The most active compound (78, Fig. 8) showed superior anti-tubercular potency against M. tuberculosis H37Ra dormant, with IC 50 and MIC values of 1 and 3 µg/mL, respectively.…”
Section: Anti-tubercular Activitymentioning
confidence: 98%
See 1 more Smart Citation
“…The in vitro anti-tubercular properties of the triazole-indole hybrid derivatives were evaluated against M. tuberculosis H37Ra in the active and dormant state. 107 The most active compound (78, Fig. 8) showed superior anti-tubercular potency against M. tuberculosis H37Ra dormant, with IC 50 and MIC values of 1 and 3 µg/mL, respectively.…”
Section: Anti-tubercular Activitymentioning
confidence: 98%
“…Neuroprotective and Alzheimer's disease agents based on 1,2,3-triazole units(105)(106)(107)(108)(109)(110)(111)(112)(113)(114)(115).…”
mentioning
confidence: 99%
“…[ 61 ] Isatin–1,2,3‐triazole hybrids 20 and their bis‐1,2,3‐triazole analogs 21 not only possessed potential in vitro and in vivo anticancer activity (MCF‐7, HeLa, and HEK293 cell lines) but also demonstrated great potency against certain bacteria. [ 62,63 ] The SAR revealed that the introduction of the electron‐withdrawing (trifluoromethyl) group at meta ‐position of the phenyl ring and bromo group at ortho ‐position of the phenyl ring had a great influence on the antibacterial and anticancer activity. Among them, hybrids 20a (MIC: 4.68 μg/ml against P. vulgaris ), 20b (MIC: 2.34 and 4.68 μg/ml against E. coli and B. subtilis ), 21a (MIC: 2.34 and 1.17 μg/ml against S. aureus and B. subtilis ), and 21b (MIC: 1.17 and 2.34 μg/ml against E. coli and B. subtilis ) displayed excellent activity against certain strains, and the activity was comparable to or better than that of streptomycin (MIC: 3.12–6.25 μg/ml).…”
Section: Indole/isatin–azole Hybridsmentioning
confidence: 99%
“…All compounds were tested against an attenuated strain ( M.tb H37Ra), in both active and dormant state. Compound 19 ( Figure 7 ) proved to be the most potent, with an IC 50 of 0.12 µg mL −1 for nonreplicating bacilli [ 181 ].…”
Section: Targeting Nonreplicating Mtbmentioning
confidence: 99%